2006
DOI: 10.1007/s00005-006-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variations of histamine binding to lymphocytes and neutrophils and skin reactivity to histamine in atopic and healthy subjects

Abstract: In the asthmatic group these changes were not significant. Circadian changes in both the binding of histamine by effector cells and skin reactivity to histamine were different in healthy and asthmatic subjects, and this may play a role in the pathomechanism, course, and chronopharmacotherapy of atopic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In healthy humans, plasma levels of beta-endorphins (but not of histamine ( 454 )) show rhythmic regulation being highest in the morning and reduced in the night ( 455 457 ). Ligand binding to histamine receptors on leukocytes likewise changes from night to day with complex patterns in healthy and atopic individuals ( 458 ). Moreover, in healthy individuals blood levels of cortisol and beta-endorphins are coupled, meaning that cortisol follows beta-endorphin with a lag-phase of ten minutes ( 459 ).…”
Section: Candidate Neuroendocrine Mediators Linking Shift Work With S...mentioning
confidence: 99%
“…In healthy humans, plasma levels of beta-endorphins (but not of histamine ( 454 )) show rhythmic regulation being highest in the morning and reduced in the night ( 455 457 ). Ligand binding to histamine receptors on leukocytes likewise changes from night to day with complex patterns in healthy and atopic individuals ( 458 ). Moreover, in healthy individuals blood levels of cortisol and beta-endorphins are coupled, meaning that cortisol follows beta-endorphin with a lag-phase of ten minutes ( 459 ).…”
Section: Candidate Neuroendocrine Mediators Linking Shift Work With S...mentioning
confidence: 99%
“…Cutaneous immune responses to allergens differ throughout the day, e.g., Reinberg et al (1965) observed that there is a circadian variation to the reactivity to skin tests. Zak-Nejmark et al (2006) et al studied skin reactivity of healthy and atopic individuals to histamine and observed that healthy individuals have the lowest reactivity at night. In contrast atopic individuals exhibit the highest reactivity at night.…”
Section: Functional Chronobiological Rhythms Of the Skinmentioning
confidence: 99%